The Frisch elasticity in the Mercosur countries: A pseudo-panel approach - Roberto González; Hector Sala (Institute for the Study of Labor (IZA), 2011)
This paper provides estimates for the Mercosur countries of the Frisch elasticity - i.e., the elasticity of substitution between worked hours and real wages holding constant the marginal utility of wealth. We find a strong heterogeneity, with estimated elasticities ranging from 12.8 in Argentina to -13.1 in Paraguay. Brazil and Uruguay are in between, both with negative values of -1.9 and -1.4, respectively. We argue that the existence of severe liquidity constraints is the main reason behind the negative estimates found in Brazil, Paraguay and Uruguay. The heterogeneity of these estimates is the outcome of differences in many relevant economic dimensions - ranging from sectorial specialization to welfare state provisions and labor market specificities - all of them crucially affecting the socioeconomic situation of individuals. The diversity of Frisch elasticities calls for the development of a cross-country (rather than a within-country) policy approach, since they crucially affect the dynamics of the business cycle and business cycle synchronization is a step prior to the design of macro-convergence policies in the Mercosur context.
urn:nbn:de:101:1-201110263314
Keywords: J22; J82; D91; 330; Frisch elasticity; labor supply; liquidity constraints; Mercosur; life-cycle models; pseudo-panel (synthetic panel); Arbeitszeit; Reallohn; Substitutionselastizität; Arbeitsangebot; Verschuldungsrestriktion; Lebenszyklus; Schätzung; MERCOSUR-Staaten